2001
DOI: 10.1073/pnas.061021998
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral RNA identified in the cerebrospinal fluids and brains of individuals with schizophrenia

Abstract: S chizophrenia is a pervasive neuropsychiatric disease of uncertain etiology. In the United States, schizophrenia has a lifetime prevalence of greater than 1% and results in the annual expenditure of more than 65 billion dollars (1, 2). Family and adoption studies have demonstrated a significantly increased risk of schizophrenia in individuals who have a first-degree birth relative with this disease, indicating that there is a substantial genetic component in disease pathogenesis. Epidemiological studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
216
0
9

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(233 citation statements)
references
References 48 publications
8
216
0
9
Order By: Relevance
“…Alternatively, as nonintact retroviral sequences may retain their ability to be retrotransposed by active transposons nearby during embryogenesis 32 , retrotransposon activity could have introduced the observed mosaicism. Moreover, as L1-activity has been implicated in neurological diseases 37 and retroviral RNAs have been linked to schizophrenia 38 , this SNV may confirm a potentially relevant disease mechanism contributing to schizophrenia.…”
Section: Discussionmentioning
confidence: 73%
“…Alternatively, as nonintact retroviral sequences may retain their ability to be retrotransposed by active transposons nearby during embryogenesis 32 , retrotransposon activity could have introduced the observed mosaicism. Moreover, as L1-activity has been implicated in neurological diseases 37 and retroviral RNAs have been linked to schizophrenia 38 , this SNV may confirm a potentially relevant disease mechanism contributing to schizophrenia.…”
Section: Discussionmentioning
confidence: 73%
“…Viral infection could be the primary insult leading to elevation of central inflammatory cytokines, such as IL-6. Karlsson et al (2001) found retroviral sequences in the CSF of 18.6% acute-onset schizophrenics and 5% of chronic schizophrenics. No such sequences were found in the normal control group.…”
Section: Commentmentioning
confidence: 93%
“…These are both heavily methylated and placentally expressed endogenous retroviral-related human genome sequences. Although no direct evidence exists for any causative effect of SZRV1 and 2 on schizophrenia, these retroviruses may be abnormally expressed in the cerebrospinal fluid of individuals with recent-onset schizophrenia or schizoaffective disorder [Karlsson et al, 2001]. In one affected patient, but none of the controls, loss of DNA methylation of SZRV2 was observed [Deb-Rinker et al, 2002], suggesting that DNA methylation may restrict placentally expressed retroviral sequences as part of natural nuclear host defences against parasitic sequence elements such as viruses [Deb-Rinker et al, 2002].…”
Section: Epigenetic Regulation Of Gene Expressionmentioning
confidence: 97%